2019
DOI: 10.1186/s12877-019-1299-4
|View full text |Cite
|
Sign up to set email alerts
|

The impact of an orthogeriatric intervention in patients with fragility fractures: a cohort study

Charlotte Abrahamsen,
Birgitte Nørgaard,
Eva Draborg
et al.

Abstract: Background While orthogeriatric care to patients with hip fractures is established, the impact of similar intervention in patients with fragility fractures in general is lacking. Therefore, we aimed to assess the impact of an orthogeriatric intervention on postoperative complications and readmissions among patients admitted due to and surgically treated for fragility fractures. Methods A prospective observational cohort study with a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
18
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 37 publications
3
18
0
1
Order By: Relevance
“…This could be interpreted as orthogeriatric treatment especially preventing early readmissions while having a lesser impact with longer follow-up. According to one previous study, orthogeriatric treatment has been associated with decreased mortality and a lower readmission rate [33] whereas such association has not been reported in other studies [2], including a randomized controlled trial [14]. In all these studies, the orthogeriatric intervention has lasted longer than in our study (i.e., for 1.5-2 weeks), and we are not aware of earlier studies concerning the effect of very short orthogeriatric intervention, like ours, on readmission rates, mortality or clinical outcomes.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This could be interpreted as orthogeriatric treatment especially preventing early readmissions while having a lesser impact with longer follow-up. According to one previous study, orthogeriatric treatment has been associated with decreased mortality and a lower readmission rate [33] whereas such association has not been reported in other studies [2], including a randomized controlled trial [14]. In all these studies, the orthogeriatric intervention has lasted longer than in our study (i.e., for 1.5-2 weeks), and we are not aware of earlier studies concerning the effect of very short orthogeriatric intervention, like ours, on readmission rates, mortality or clinical outcomes.…”
Section: Discussionmentioning
confidence: 84%
“…Hip fractures are a common and costly injury worldwide [ 1 ]. In older patients, hip fractures have also been associated with increased morbidity [ 2 ] and increased health care costs [ 3 ], and increased mortality [ 4 , 5 ]. From patients’ point of view, hip fracture often leads to decline in quality of life and functional ability and consequently there’s an increased need for assistance in daily living and many patients move to more assisted living environments [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to our results, it has been shown that the implementation of multidisciplinary care improves clinical outcome of elderly patients after hip fracture [ 19 , 42 ]. Despite some literature indicating no advantages of ortho-geriatric interventions [ 43 ], the majority of published studies support GC by showing improved outcomes [ 40 , 42 , 44 ]. The advantages of interdisciplinary comanagement is mirrored by the comparable mortality despite increased medical complexity.…”
Section: Discussionmentioning
confidence: 99%
“…Orthogeriatric care of injured old patients has been shown to have a positive influence on treatment’s outcome. 14 …”
Section: Introductionmentioning
confidence: 99%